ANALISA TINGKAT CACAT PADA PROSES PENGELASAN DENGAN METODE SIX SIGMA DAN FAILURE MODE AND EFFECTS ANALYSIS (FMEA) - Irwan, Hery; Afma, Vera Methalina; Ramadhan, Gilang (SIGMA TEKNIKA, 2025)
Welding is an important process in the shipbuilding industry that affects the strength and safety of ship structures. At PT BVS, the Flux Cored Arc Welding (FCAW) process still produces a high defect rate, particularly types of defects such as porosity, slag inclusion, undercut, root concavity, and lack of fusion. Based on data from January to May 2025, the reject rate reached 56%, far exceeding the company's standard of 10%. This study aims to identify the types and causes of defects in FCAW welding, as well as provide improvement proposals using the Failure Mode and Effects Analysis (FMEA) method. The analysis show that the three causes with the highest RPN values come from human factors, methods, and machines. Improvement proposals include operator training, preparation of welding Standard Operating Procedures (SOP), regular equipment condition checks, and adjustment of welding parameters. The implementation of these improvement proposals is expected to reduce the defect rate, improve the quality of welding results, and minimize rework costs and production delays. This study provides practical contributions for companies in enhancing welding quality and serves as a reference for quality control in the shipbuilding industry.